Economics Beyond Markets: Choice Experiments in Developing Countries - Bennett, Jeff (2010)
June 21, 2010 IFPRI Policy Seminar Washington, DC Economics Beyond Markets: Choice Experiments in Developing Countries Jeff Bennett Ekin Birol Derek Byerlee